Efektivitas KKN Tematik Posdaya Berbasis Masjid Bagi Pemberdayaan Masyarakat - Emi Hidayati (Jurnal Ilmiah Ar-Risalah: Media Ke-Islaman, Pendidikan dan Hukum Islam, 2013)
It is important to measure the success, the benefits andoutcomes of the implementation of the Working Class Real (KKN)as a form of community service, which is integrated in thecurriculum of higher education, in order to achieve the goals andexpectations for students as a degree candidate, for thecommunity as beneficiaries and for universities as agenciesmandate bearers Tri Darma Higher Education. So in order todesign guidelines as the direction and flow of the implementationof the thematic KKN Based Posdaya this mosque, LPPM taskedto implement the program are supposed barsandar to the basicprinciples and rules - the rules imposed by reference. Referencesinclude Law No. 12 of 2012 on Higher Education andPermendikbud No. 49 Year 2014 on National Standards for HigherEducation, History of corruption, and by adjusting the educationalphilosophy embodied in the mission of institutions, as well as thebasic concepts of movement Posdaya Based mosque becomesthe spirit of community empowerment movement. By taking thetheory and the concept of effectiveness, community empowermentand CCN Posdaya Masjid based and History learning programs,is expected to inspire the author personally and readers tocontribute to improving the pattern of movement of the devotion ofstudents at this institution, in order to continue to improve thequality of service for the benefit of the Ummah.